Colour Removal of Distillery Waste by Saccharomyces in Combination with Fungal Strains - RAJOR, A.; SINGH, R. (Asian Journal of Chemistry, 2010)
In distillery, sugars are fermented to alcohol through yeast. During fermentation all the sugars do not get utilized and some shown in the discharged liquid called spent wash. The yeast (Saccharomyces cervisiae) has the ability to utilize the non-reducing sugars involving enzymatic reactions. Fungi are recognized for their superior aptitudes to produce a large variety of extra cellular proteins, organic acids and other metabolites. That is why mixed culture of fungus and yeast was studied with concentrations of supplemented carbon source as 0.1, 0.05 and 0.02 %. The COD and colour removal observed in between 47.9- 50.6 % and 60.8-53.1 %, respectively with yeast + Rhizomucor pusillus, whereas it was 47-69 % and 54.4-65.7 % yeast + Rhizopus microsporus with 0.1, 0.05 and 0.02 % glucose, respectively in 48 h. Most research or fungal capacities to purify polluted effluents has been performed on a laboratory scale, hence there is a need to extend such research to pilot scale and to apply it to industrial process.